PENINGKATAN MINAT BELAJAR SISWA MELALUI STRATEGI PEMBELAJARAN INQUIRING MINDS WANT TO KNOW PADA MATA PELAJARAN IPS SD - Amri Nurhidayat; Diva Adelia; Indah Widiani; Rica Amelia Putri; Sheila Syalma Safitri; Arita Marini (Bajang Institute, 2023)
Implementing active, effective and diverse learning strategies can help students achieve academic results. Learning outcomes are the ultimate goal of implementing learning activities at school. Improving learning outcomes can be done through conscious efforts that are carried out systematically and lead to positive changes which are then called the learning process. Student learning outcomes in the classroom are collected into a set of class learning outcomes. All of these learning outcomes are the result of the interaction between teachers and students in the teaching and learning process